Diurnal and semi-diurnal coordinate variations observed in EUREF permanent GPS network – a case study for period from 2004.0 to 2006.9 - HEFTY, Ján; IGONDOVÁ, Miroslava (Contributions to Geophysics and Geodesy, 2010)
The 2.9-year interval of homogeneous and continuous observations at 29 Europeanpermanent GPS stations distributed all over the whole continent is analyzed forthe short-periodic variations of site coordinates. In the literature seasonal terms in GPScoordinate series are well documented; the main objective of this paper is to investigatethe existence of variations with shorter periods. We used the coordinate estimatesobtained from 4-hour observing intervals which enabled identification of variations withdiurnal and sub-diurnal periods. In the amplitude spectra of station time series we detecteda set of dominant periodic terms which have exclusively diurnal and semi-diurnaltidal frequencies. The most significant are the diurnal S1, K1, O1 and semi-diurnal S2,K2, M2 waves. Their amplitudes are different for individual sites and they reach fromsub-millimetre values up to ∼ 3 mm for some stations situated close to the Atlantic coast.Uncertainties of estimated amplitudes are generally at the 0.3 mm level. The possibleorigin of the observed periodic variations is very complex. We interpret the observedcoordinate variability as a superposition of potential deficiencies in used models of oceantide loading displacements, effects of atmospheric tides, multipath, troposphere and ionosphereresidual effects, and other phenomena with diurnal and semi-diurnal forcing as wellas the unidentified GPS analysis imperfection. The geokinematical relevance of detectedvariations and their possible interpretation are discussed.